Some Plant Food Products Present on the Polish Market Are a Source of Vitamin B12 - Paulina Jedut (Applied Sciences, 2021)
Cyanocobalamin is the most widespread form of vitamin B12, which is sufficient for humans. Vitamin B12 is mainly found in animal products. However, supplementation does not have to be necessary because certain amounts of vitamin B12 are present in plant products. Previous studies showed significant contents of cyanocobalamin in sea buckthorn and in sauerkraut. In this study, selected products such as sea-buckthorn jam and fermented plant products (obtained by lactic acid fermentation) were tested in a search for vitamin B12. Bacteria involved in this type of fermentation have the potential to produce cyanocobalamin. Popular fermented plant products on the Polish market were selected, namely sauerkraut and pickled cucumbers, as well as parsley juice, beetroot juice and white borscht. The analysis was carried out using HPLC-UV. Most of the analyzed products did not contain significant levels of vitamin B12. Only sea-buckthorn jam and pickled parsley juice can provide the amount of vitamin B12 needed to prevent deficiency.